Direct ethanol fuel cell as aircraft APU: a study for onboard waste heat recovery - de Almeida Ramsdorf, Marcelo; Matelli, José Alexandre [UNESP] (Springer Nature, 2018)
An advanced concept of jet aircraft (known as “more electric aircraft”) available nowadays requires electrically driven systems. In this scenario, application of low-temperature fuel cells in aircraft is an interesting alternative to generate power for the electrically driven systems with high efficiency and low environment impact. However, hydrogen fuel cells pose difficulties for aircraft designers due to safety and weight requirements related to onboard use of hydrogen. Direct ethanol polymer fuel cells (DEPFC) may overcome such difficulties, but recent publications show that DEPFC still presents low efficiency and, therefore, generates high amounts of waste heat. In this work, the use of a DEPFC as auxiliary power unit (APU) in a regional jet is proposed and opportunities for onboard waste heat recovery are evaluated. Obtained results suggest that heat recovery from DEPFC is technically feasible for cabin heating, fuel heating, and water onboard production.
Keywords: Aircraft; Ethanol; Fuel cell; Heat recovery